Human Rights in the Border Society of the North-North Territory: Protection within Costa Rican Legislation - Carvajal Jiménez, Vivian Rebeca (2022)
The protection of fundamental human rights is key to the democratic life, peace, and social justice of nations. Costa Rica prides itself all over the world for the strength of its social rule of law and the protection it grants to its residents, whether nationals or foreigners. However, in the case of the border society in the north-north of the country, there are vulnerable population groups from various sides (migration, poverty, symbolic barriers, low schooling) that see their full experience of rights overshadowed. Considering national and international legislation, this text reflects on the legal framework that guarantees rights, such as health, education and work for individuals residing in the border society, contrasting it with the main challenges for its compliance.